Public Service Motivation, Integrity, and Performance: A Mediational Analysis in Civil Registration Services - Saputra, Boni; Syeftiani, Try; Gomes da cruz Fernandes, Benjamin; K. Ethelbert, Yohanes (Universitas Terbuka, 2025)
The persistently low quality of public services in Indonesia remains a critical issue, as highlighted by 2024 Indonesian Ombudsman data showing a high volume of public complaints, primarily concerning bureaucratic personnel behavior lacking public orientation and integrity. This study examines the influence of public service motivation and integrity on employee performance, with job satisfaction as a mediating variable, focusing on the Population and Civil Registration Office (Disdukcapil) in West Pasaman Regency. Adopting a quantitative, associative approach, the study surveyed 58 respondents selected via simple random sampling from a total population of 61 employees. Data were collected using a structured questionnaire based on a 5-point Likert scale and analyzed through path analysis. The findings indicate that both public service motivation and integrity significantly positively impact employee performance, directly and indirectly, through job satisfaction. Integrity emerged as the most influential factor affecting performance (β = 0.934; R² = 0.873), followed by job satisfaction (β = 0.925; R² = 0.856) and public service motivation (β = 0.891; R² = 0.795). This study underscores the urgent need for human resource development strategies emphasizing integrity and public service motivation while fostering a supportive work environment to enhance job satisfaction. By identifying key behavioral drivers of employee performance in local government institutions, the research contributes to the broader discourse on bureaucratic reform. It offers actionable insights for improving public service delivery in Indonesia.